2018
DOI: 10.17126/joralres.2018.066
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation trends among members of the Chilean Endodontic Society

Abstract: Introduction: The aim of this study is to determine the current trends of irrigation during root canal therapy by specialists who are members of the Chilean Endodontic Society. Materials and Method: A survey (Survey Monkey®-SurveyMonkey.com) was e-mailed to the 485 members of the Chilean Endodontic Society. The instrument was translated and adapted from the survey "Irrigation trends among American Association of Endodontists members: A web-based survey" applied in the USA in 2012. Participants answered a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Manual activation may be favored over ultrasonics because it is a low-cost technique that does not require special devices. This finding is similar to that obtained by Monardes et al [34], who reported that most of their respondents used manual activation.…”
Section: Discussionsupporting
confidence: 92%
“…Manual activation may be favored over ultrasonics because it is a low-cost technique that does not require special devices. This finding is similar to that obtained by Monardes et al [34], who reported that most of their respondents used manual activation.…”
Section: Discussionsupporting
confidence: 92%